Tracing the Orogenic Sulfur Cycle in the Andes Using Stable Isotope Composition of Dissolved Sulfate in Thermal Springs - Blamey-Alegria, J (Elsevier B.V., 2024)
The cycling of sulfur (S) to the upper crust and surface via thermal springs at convergent margins has not been explored outside areas with active arc volcanism, even though subduction plays a key role in the Earth s long-term S cycle. To address this knowledge gap, we analyzed stable sulfur and oxygen isotope compositions (δ34S and δ18O values) of dissolved sulfate (SO42−) in 55 thermal springs from five distinct settings in the Andean orogen. These regions are the Peruvian flat slab and backarc, transition between these two, Argentinian backarc, and Chilean forearc. Although the flat-slab settings had lower SO42− concentrations (<2000 mg/L) compared to the steep-slab settings (<12,700 mg/L), there was no significant relationship between isotope composition of SO42− and slab geometry. The δ34S and δ18O values of SO42− varied widely across the studied areas (+0.2 to +23.5 ‰ and − 3.3 to +16.0 ‰, respectively) and reflected the isotope compositions of local bedrock endmembers from dissolution of marine evaporites (+5 to +25 ‰ and + 10 to +20 ‰, respectively) and oxidation of magmatic and/or hydrothermal S and ore sulfide minerals with variable δ34S (0 to +16 ‰). The δ18O and δ2H values of thermal spring water (−18.5 to −3.3 ‰ and − 141.1 to −23.7 ‰, respectively) were consistent with meteoric precipitation, and in most cases decreased with increasing altitude following precipitation in the Andes. Generally, our isotope results do not support the direct transfer of slab-derived S/SO42− to thermal springs in the investigated settings. Rather, the δ34S and δ18O of SO42− in the thermal springs are a sensitive indicator of local water-rock interactions that remobilize bedrock S originating from a complex orogenic cycle reflecting tectonic uplift, erosion, weathering, and exhumation history across the duration of Andean Mountain building. © 2024 Elsevier B.V.